LOOKING BACK TO THE BYGONE DAYS - Qodiriy Mahzuna Shavkataliyevna (Journals Park Publishing, 2022)
The work is based on the example of Abdulla Qodiriy’s work "The Bygone days ". It is possible to achieve effective results by studying such issues as advanced hybrid linguistics, aesthetic taste, faith in world linguistics studies. Hybrid linguistics criteria of the works Abdulla Qodiriy, who made his contribution to our national literature to study his life and work as a whole, to study the artistic skills of the writer, the vital and creative factors he created from the perspective of linguistic devices made us to convey the meaning of author’s words. Today in research linguistics it is one of the most important issues .
Keywords: manners,language,history, uzbek traditions, linguistic pecularaties.